2017
DOI: 10.3390/ijms18091907
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal and Circulating MicroRNAs in Coeliac Disease

Abstract: MicroRNAs (miRNAs) are short non-coding RNAs that regulate gene expression at the post-transcriptional level and play a key role in the pathogenesis of autoimmune and gastrointestinal diseases. Previous studies have revealed that miRNAs are dysregulated in intestinal biopsies of patients affected by coeliac disease (CD). Combined bioinformatics analyses of miRNA expression profiles and mRNA target genes as classified by Gene Ontology, are powerful tools to investigate the functional role of miRNAs in coeliac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Recent reports have demonstrated that specific miRNAs are modulated in duodenal mucosa affected by CD. The miRNAs dysregulated during the development of CD could be potentially involved in the pathogenesis of CD [6]. Overexpression or downregulation of several miRNAs could potentially stimulate or inhibit pathways related to the pathogenesis of CD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have demonstrated that specific miRNAs are modulated in duodenal mucosa affected by CD. The miRNAs dysregulated during the development of CD could be potentially involved in the pathogenesis of CD [6]. Overexpression or downregulation of several miRNAs could potentially stimulate or inhibit pathways related to the pathogenesis of CD.…”
Section: Introductionmentioning
confidence: 99%
“…CD is a genetic autoimmune disorder mainly affecting the small intestine, elicited by an aberrant inflammatory response to dietary gluten proteins found in wheat, rye and barley [27,[162][163][164].…”
Section: Can Fecal Mirnas Be Celiac Disease Biomarkers Interacting Wimentioning
confidence: 99%
“…Additionally, more than 90% of human Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways contain genes that are targeted by at least one miRNA [19,25]. The partial or full complementarity of a miRNA with the mRNA target regulates the expression of target genes generally in a negative manner causing their degradation or translational inhibition [26,27]. Therefore, an upregulation of a specific miRNA generally leads to a lower expression of the protein encoded by its mRNA target, whereas the downregulation of a specific miRNA could lead to higher protein levels [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, little is known about the presence of reliable circulating microRNA biomarkers to diagnose the disease or to monitor the progression or remission after a gluten-free diet. In order not to lengthen the present review with a detailed description of the studies dealing with this important pediatric disease, we collected and discussed the papers about circulating microRNAs and celiac disease in a recent paper [ 81 ].…”
Section: Circulating Micrornas In Plasma/serummentioning
confidence: 99%